Handbook of optical metrology principles and applications - Yoshizawa, Toru 1939- (Taylor & Francis, CRC Press, 2015)
This new Second Edition is fully revised to reflect the latest developments. It also includes four new chapters-nearly 100 pages-on optical coherence tomography for industrial applications, interference microscopy for surface structure analysis, noncontact dimensional and profile metrology by video measurement, and optical metrology in manufacturing technology